Oropharyngeal tularemia mimicking tumoral relapse in a patient with Hodgkin lymphoma in remission - Incesoy-Ozdemir, Sonay; Bozkurt, Ceyhun; Oren, Ayşe Ceyda; Balkaya, Eda; Yüksek, Nazmiye; Sahin, Gürses; Ertem, Ulya (The Turkish Journal of Pediatrics, 2011)
Tularemia is a zoonotic disease caused by Francisella tularensis. The clinical forms mostly depend on the port of entry into humans. Ingestion typically results in the oropharyngeal form and is associated with symptoms such as fever, pharyngitis, cervical lymphadenitis, and suppuration. In this report, we describe a child treated for Hodgkin’s disease presenting six years later with a left cervical lymphadenopathy mimicking a relapse.